Calendar Anomalies in the GCC Equity Markets - Gharaibeh, Omar (Jordan Journal of Business Administration, 2021)
This paper examines calendar anomalies for Gulf Cooperation Countries (GCC) stock markets (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, Abu Dhabi and Dubai) using the closing price indices for these markets during the period 2012-2017. Three well-known calendar effects are examined; the day of the week effect, the monthly effect and the turn of the month effect (TOM). This paper documents that the Monday effect is prominent in Bahrain index in both OLS and GARCH (1, 1) equations, while this effect exists in GARCH (1, 1) equation for Kuwait. The study also shows that Wednesday provides a statistically significant return in Abu Dhabi, while Thursday achieves a statistically significant return in Bahrain, Saudi Arabia and Dubai based on the OLS and GARCH (1, 1) models. For the month of the year effect, this paper provides evidence of the January effect in both OLS and GARCH (1, 1) equations for Kuwait, which is consistent to the findings of previous studies. In contrast, the effects for the three Gulf equity markets (Qatar, Abu Dhabi and Dubai) are limited and exist only in GARCH (1, 1). The Oman stock market provides clear evidence of the TOM effect due to OLS and GARCH (1, 1) models, while this effect seems to be existent in Qatar and Dubai based on only GARCH (1, 1) coefficients. This inconsistent evidence among Gulf markets can be based on the different level of liquidity and the evolution of these markets. Both decision makers and investors should take these anomalies into consideration for outstanding investment performance.